KOMUNIKASI BAHASA DALAM KONTEKS SOSIAL DAN BUDAYA: STUDI KASUS INTERAKSI MULTIKULTURAL DI PERGURUAN TINGGI - Moh. Syamsul Ma’arif; Siti Nur Afifatul Hikmah (Jurnal PENEROKA, 2026)
The aim of this study is to understand in depth the dynamics of language communication in the context of multicultural interaction in a higher education environment, with a focus on KH University. Mukhtar Syafaat Blokagung Banyuwangi. The diversity of students' linguistic and cultural backgrounds at UIMSYA, this research explores the forms of language communication interaction that are realized, the challenges of understanding that arise due to linguistic and cultural differences, as well as the communication adaptation strategies used by students. Data collection techniques through observation and structured interviews focused on Tadris Bahasa Indonesia students in semester 4. Data analysis, researchers used the Miles and Hubermen flow chart which includes data collection, data reduction, data presentation, and conclusions/verification. The data found based on themes relevant to the data revealed linguistic flexibility in the use of Indonesian and regional languages, the potential for miscommunication due to differences in dialects and cultural references, as well as various accommodation strategies implemented by students to bridge differences. The implications of these findings highlight the importance of awareness of language diversity, development of cross-cultural communication competencies, and creation of an inclusive academic environment to maximize the positive potential of multicultural interactions in higher education.